STRATEGI PENGEMBANGAN USAHATANI PADI SAWAH DI DESA TEGALGONDO KECAMATAN KARANGPLOSO KABUPATEN MALANG - Malo, Ferdinan; Nugroho, Anung Prasetyo; Rofiatin, Umi Rofiatin (Universitas Tribhuwana Tunggadewi, 2024)
The research aims to determine internal and external factors in the development of lowland rice farming and to develop a strategy for developing lowland rice farming in Tegalgondo Village, Karangploso District, Malang Regency. Data collection techniques are obtained from questionnaires and documentation. The data analysis method used was internal and external factors. The results of research on alternative strategies for developing lowland rice farming that can be carried out by the government in Tegalgondo Village are the S-O strategy with expanding better types of superior varieties from time to time and developing partnerships with other farmer groups, W-O Strategy: working together with farmer groups and agricultural services to improve the quality of business, knowledge, skills of farmers, agricultural technology, infrastructure, sources of capital and market information, S-T strategies such as form farmer groups to overcome changes in markets and prices and establish partnerships with other parties industry and marketing, W-T strategy with strengthening farmer cooperatives and market information networks and air management and sustainable agricultural practices.